Comparative evaluation of inter appointment pain and analgesic intake with calcium hydroxide and triple antibiotic paste as intracanal medicaments in patients with apical periodontitis – a randomized controlled single-blinded clinical trial: Interappointment and analgesic intake on using two different medicaments - Narayanan, Sanu; Venkata Teja, Kavalipurapu; Ramesh, Sindhu (Brazilian Dental Science, 2022)
Objective: This study aimed to evaluate the effect of calcium hydroxide and triple antibiotic paste as intracanalmedication on the interappointment pain at 8, 24, and 48 hours postoperatively in patients with symptomaticapical periodontitis undergoing multiple visit root canal treatment. Material and Methods: Two hundred andseven systemically healthy patients under the age group of 18-45 years with mandibular molars presenting withsymptomatic apical periodontitis which require root canal treatments were included in this study. After accesscavity preparation, cleaning and shaping was done till ISO 25 size file, and the patients were randomized intothree groups (each group of 69 samples). Group I: no medicament, group II: calcium hydroxide and group III:triple antibiotic paste (TAP). Postoperative pain was evaluated at 8 hours, 24 hours and 48 hours. Results:The results showed that at 8 hours, 24hours and 48hours, there was a statistical difference between I and III(p < 0.05); and Group III and Group II (p < 0.05). Within the group, there was a statistical difference at alltime points IN Group I and II (p < 0.05) except between 24 hours and 48 hours in the Group III (p > 0.05).Conclusion: Within the limitations of this study, TAP was more effective than calcium hydroxide in relievingpain and reducing the analgesic intake at the first 24hours.KEYWORDSIntracanal medicament; Calcium hydroxide; Triple antibiotic paste; Interappointment pain; Apical periodontitis.